Upaya Ustadz/Ustadzah Meningkatkan Pemahaman Thoharoh Pada Santri Putri Kitab Fathul Qorib Karya Ibnu Qosim Al-Ghazy di Pondok Pesantren Hidayatul Mubtadiin - Oktavia Nurul Maida (Departement of Mathematics Education, 2024)
This thesis discusses the efforts to learn the Fathul Qorib book and its role in strengthening the subject of the Fathul Qorib book for female students of Hidayatul Mubtadiin. The type of research approach is an empirical legal approach or field research. The data collection techniques used are observation, interviews, and documentaries. Data analysis used in this study uses descriptive-qualitative. Researchers test and ensure the validity of the data using triangulation techniques. Based on the results of the study, it can be concluded that: (1) efforts to learn the Fathul Qorib book use the Balah method, the Lecture method, and the Question and Answer method. (2) the impact of implications, namely environmental factors, electronic goods factors, and friend factors. The results of this study indicate that learning the Fathul Qorib book in Islamic boarding schools is carried out on Mondays every week after the Isyak prayer. The learning method used is the Balah method. In its learning, the Fathul Qorib book itself is taught in an integrated manner both in terms of Javanese and Arabic and in terms of the science of Islamic jurisprudence itself. The efforts of ustadz/ustadzah to improve the understanding of female students of the Fathul Qorib book from the Thoharoh material to the hajj taught at the Hidayatul Mubtadiin Islamic boarding school are considered to be able to provide an influence in terms of the depth of knowledge and understanding of students, and this is done by looking at the material needs of students taught at the boarding school.